Աբդուրրահման Շերեֆ. Թանզիմաթից մինչև Հանրապետություն - Հովհաննիսյան, Անուշ (Ասողիկ հրատ.)
The article is dedicated to the analyses of the biography of Abdurrahman Sheref, the last Chronist of the Ottoman Empire. His life (1853-1925) and activities coincided with the crucial period of the Turkish history, marked with the decline of Empire, Itühadist bloody adventurous rale, Kemalist nationalist movement and declaration of Turkish Republic. All these evesnts among others had their effect on the foundation of Turkish national historiography too.
Keywords: Պատմություն; Քաղաքականություն